If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4()3x+1=-2(5x-2)
We move all terms to the left:
4()3x+1-(-2(5x-2))=0
We calculate terms in parentheses: -(-2(5x-2)), so:We get rid of parentheses
-2(5x-2)
We multiply parentheses
-10x+4
Back to the equation:
-(-10x+4)
4()3x+10x-4+1=0
We add all the numbers together, and all the variables
10x+4()3x-3=0
We move all terms containing x to the left, all other terms to the right
10x+4()3x=3
| 3a+a=1.60 | | 3a=1.60 | | a+a=1.60 | | a4=1.60 | | 6b+4=-2b-16 | | 79.8=7(m+3.6) | | 0=5x^2-7x+9 | | 4a=1.60 | | 10x+13=5x+76.5 | | 3x-13=4(x-4) | | 79.8=7(m+3.6 | | 2(-7x+2)=4 | | -6(2-x)+3(x-4)=12 | | 4y+7+y=10+3y | | s+s=18 | | -282=-6(5+7x) | | n=3•45 | | s/2=18 | | 1800-×=3x | | -4(2x+4)=104 | | 23=4×t-7-t | | 5x+5=80+5x | | -90=5(7x+10) | | 8x-2x+64=8x+30 | | 21⋅3=g | | 16x+x=180 | | g/3=21 | | 2/3x=-3/10 | | -2.2+0.3z=3+0.3z | | -10x+2=-124+11x | | 10x+2+5+3x=180 | | x÷3+3+4=17 |